The effect of hydroxide ions on the electrocatalysis of glucose at single platinum nanoparticles - Lin, Jun; Wang, Jun; Li, Shuang; Zhao, Wenbin; Zhang, Dong; Zang, Yue; Xin, Qing (Journal of applied electrochemistry, 2023)
Glucose oxidation on platinum nanoparticles (Pt NPs) at varying potentials (from − 0.7 V to 0.2 V) was investigated using single entity electrochemistry. The active chemisorption model was found to be valid only at potentials below − 0.6 V, while the incipient hydrous oxide/adatom mediator (IHOAM) model was confirmed for potentials above − 0.6 V. In both cases, hydrous ions significantly improved glucose oxidation by freeing up active sites on the Pt NPs. The potential for glucose sensing at − 0.4 V, where continuous glucose oxidation took place, was assessed. Although the linearity was limited (0.1–0.6 mM), the high sensitivity of 423.056 µA mM − 1 cm − 2 and limit of detection (LOD) of 25.63 µM demonstrated promising prospects for glucose sensing at − 0.4 V, particularly for samples with low glucose concentrations. Graphical abstract